(untitled) (Research, Society and Development, 2021)
The energy content is the most expensive component in the diet for production of swine. In this context, the objective of this study was to evaluate the profitability of nutritional plans with different net energy (NE) levels for barrows and gilts through sensitivity analysis. Nutritional plans with variable levels of NE were evaluated (2300; 2380; 2460; 2540; 2620 and 2700 kcal of NE/kg) in diets of 144 swines. The carcasses gross profit was determined based on bonus system (CGPbs) and or based solely on live weights (CGPlw). A sensitivity analysis was performed for each NE nutritional plan with different simulations of price quotes for the ingredients in the diet. The simulations carried out for the price of corn for nutritional plans for barrows, indicate that higher levels of net energy provided the highest CGPbs and CGPlw. For degummed soybean oil, the increase in the concentration of net energy in diets provided an increase of up to 6% in CGPbs and CGPlw. For gilts, the increase of energy levels in the diets from 2460 to 2700 kcal of net energy improved the gross profit by 17% when carcasses were sold based on bonus system (CGPbs) and CGPlw was higher when fed with the diet containing 2540 kcal of NE. The increase in the net energy level from 2300 to 2700 kcal in the diet of both barrows and gilts during the growth-finishing phase generated improvements in economic gains, regardless of the way in which the animals are marketed (CGPbs and CGPlw).